Exclusion of farmers as a consequence of quality certification and standardisation - Vuylsteke A.; van Huylenbroeck G.; Collet E.; Mormont M. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
During the past decades, Belgian and European agriculture encountered several crises and as a result, food safety and quality have become governmental issues. This has led to vertical coordination and the appearance of quality conventions between links in the food supply chain. In practice, the quality conventions initiated by changed institutional settings turned out to be compulsory. This research aims to assess the exclusion-effect of this process and this is undertaken through data-analysis concerning farmers' participation in certification initiatives and homogeneity analysis. The results of a survey concerning 319 Belgian farmers show that 25% of the farmers are not involved in any initiative of quality improvement. They are significantly older and less educated, but have also very little access to farmers' organisations and extension. Their gross margin is lower in comparison with participants; they are more oriented to one specialisation and are less labour intensive. The combination of these elements can be seen as a constraint to enter initiatives and as a probable danger to exclude the concerned farmers from the market. This paper further elaborates upon these results, but also studies farmers' opinion regarding laws, contracts and labels. Finally, some recommendations towards public policies are made.
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)